Absolute Properties of Arbitration Decision in Business Dispute Settlement Based on Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution Law Based on Justice Theory Perspective - aryani witasari (Jurnal Pembaharuan Hukum, 2017)
Article 2 of Law Number 30 Year 1999 concerning Arbitration and Alternative Dispute Settlement indicates that dispute settlement or disagreement among parties in a certain legal relationship shall be the authority of the arbitration institution, if it has been agreed in an arbitration agreement. This research tried to criticize the concept of absolute nature of the arbitral decision in the settlement of business dispute in the perspective of the theory of justice. Method of data retrieval used in this research was by collecting literature study by studying data and analyzing the entire contents of library by linking to existing problems. The final and legally binding arbitral decision, if associated with Aristotle's corrective theory of justice, does not at all reflect the basic value of justice. This is indicated by not giving an opportunity for another party whose position is higher to correct the decision, whereas in the judicial system, the court as an ordinary court having legal status (legal statue) and legal authority (legal authority/legal power). Verdict the panel of judges can still be corrected through the usual remedies (appeals) and extraordinary reviews.